Determination of the optimal air-fuel ratio for upgraded biogas engine operation - Dimitrov Radostin (EDP Sciences, 2021)
The paper reveals a study about air-fuel ratio variation of spark-ignition engine running on upgraded biogas (biomethane). Using biogas as internal combustion engine fuel and external mixture formation is a new approach to decrease harmful exhaust gas emissions. Тo obtain minimum concentrations of exhaust gases harmful emissions the engine must work with optimal air-fuel ratio. This research contains analysis of many test engine adjusting characteristics to determine optimal air-fuel ratio for each working regime and to obtain maximum effective working process by the use of biomethane as a fuel. Three-dimensional graphics of air-fuel ratio variation across the rpm and load range were made. In conclusion based on performed experiments, a table with values of air-fuel ratio for all engine operating modes and dependence on rpm and load of the engine is proposed.